Gut-kidney axis modulation by viable and inactivated Akkermansia muciniphila mitigates avian hyperuricemia through microbial-metabolic crosstalk - Fu, Y.; Chen, J.; Cao, Q.; Zhu, S.; Chen, W.; Luo, H.; Zhao, Y.; Lukuyu, Ben A.; Wang, X.; Tu, Q.; Zhang, Y.; Jiang, X.; et al. (American Society for Microbiology, 2025)
Hyperuricemia (HUA) has become the fourth most important health-threatening risk factor after hypertension, hyperglycemia, and hyperlipidemia, but the efficacy of existing uric acid-lowering treatments (ULT) is poor, and there is an urgent need to explore novel ULT strategies. Akkermansia muciniphila (A. muciniphila), a next-generation probiotic, shows promise in promoting intestinal homeostasis and metabolic regulation. Previous studies have demonstrated the potential application of A. muciniphila in ULT, but its specific mechanism has not been elucidated. In this study, we isolated a strain of A. muciniphila, named K101, from the cecum of goslings. In vitro experiments showed that K101 directly degrades uric acid, suggesting a potential microbial-metabolic crosstalk mechanism for anti-HUA. In vivo experiments showed that K101 increased the abundance of uric acid metabolism-related microbiota, such as A. muciniphila and Lactobacillus. Functionally, K101 synergistically promoted uric acid excretion by activating the intestinal excretory protein ABCG2 and inhibiting the renal uric acid reabsorption protein GLUT9. In addition, K101 provides a stable environment for uric acid metabolism by inhibiting renal inflammatory responses. Overall, A. muciniphila K101 exerts anti-HUA effects by remodeling the intestinal microbiota and excretion of uric acid through the gut-renal axis. This study offers new insights into microbial-metabolic crosstalk in uric acid metabolism in A. muciniphila and identifies potential targets for gout prevention and ULT strategy development.